Online Sales And Payment In Smes Financial Reporting Preparation - Ferry Kosadi; Wajib Ginting; Muhammad Iqbal Alamsyah (Jurnal Reviu Akuntansi dan Keuangan, 2021)
The objective to evaluate  relationship between online sales & payment to financial preparation Small & Medium Enterprises. Ecommerce provideautomationtransaction processing through various information technology platforms can have impact in recording transaction and financial reports preparation.Quantitative research method uses Partial Least Square Structural Equation Modeling analysis with descriptive analysis of financial reporting preparation.Result, greatest positive impact Online Payment to Recording Transactions and Online Sales to Financial Statements as well as ability to explain from recording Transactions and Financial Statements in Average Determination state. Average 66.7% positive responsestoservice online features, completeness, accuracy and product sales notifications, 81% support for online payment speed & ease processing, economic value and level of use, 75% support for recording transactions on completeness, simplification and data security and 60% understanding SAK, ease of use, consistency in use, desire to increase understanding accounting and economic value in preparing formal financial reports. Constraints from online sales to financial reporting include infrastructure readiness, human resource adaptation, investment costs and  Automation implementation. Overall evidence of digital transactions makes positive contribution to recording &reporting SMEs finances and becomes part of learning in the process of increasing digital iteration and digital transformation in the accounting sector.